Twelve new species and four new records of Stenoloba Staudinger 1892 from China (Lepidoptera, Noctuidae: Bryophilinae) - Han, H.l.; Kononenko, V.s. (Zootaxa, 2018)
Twelve new species of the genus Stenoloba Staudinger, 1892 (S. gaoligonga sp. n., S. huanxipoa sp. n., S. chlorobrunnea sp. n., S. ochraceola sp. n., S. plumbeoviridis sp. n., S. plumbeobrunnea sp. n., S. cucullata sp. n., S. asymmetrica sp. n., S. acontioides sp. n., S. rectilinoides sp. n., S. uncata sp. n. and S. assimilina sp. n.) are described from China. Four species (S. albistriata Kononenko & Ronkay, S. glaucescens (Hampson), S. rectilinea Yoshimoto, and S. brunnescens Kononenko & Ronkay) are reported to China for the first time; S. nora Kononenko & Ronkay is firstly reported for the continental China. The female genitalia of five species (S. albistriata, S. brunnescens, S. plumbeoculata Pekarsky, Dvořák & G. Ronkay, S. motuoensis Han & Lu and S. acutivalva Han & Kononenko) are described and illustrated for the first time. New data on distribution in China for four species are provided. All treated species are illustrated in colour with black and white photographs of their genitalia in 56 figures. The updated global checklist of the genus Stenoloba with marking of Chinese species is presented.